(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
Within the compass of Cassian brachiopod faunas from the Ampezzan Valley (Belluno), Amphitomella hemisphaeroidica (Klipstein, 1844), a taxon noted in the literature for the abnormal development of its median septum in both valves, is analysed. This structure has been examined in detail with regard to morphology, ontogenesis and ultrastructure. Other significant diagnostic and morphofunctional characters are: brachidium, cardinalia, peripheral margin. For the first time, the presence of the saddle in the brachidium is reported, thereby changing Bittner’s reconstruction (1890). The cardinalia comprise a cardinal lamina and a cardinal pit; they are massive and probably thus fitted for the attachment of very developed diductor muscles. The anterolateral margin presents snugly fitting internal ridges and grooves and an external gutter covered by mantle; these elements reduce the gape of the shell and affect the mode of absorption of nutrients. Median septa are thus necessary for enhancing water flow through the mantle cavity.